2012
DOI: 10.3813/aaa.918546
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Methods to Estimate Urban Noise Exposure of Inhabitants

Abstract: Most of the European Member States have produced strategic noise maps according to the requirements issued by the 2002/49/EC directive (END)and after the first run the results are available on the web.Astraightforward comparison of estimated noise exposure data in each country is meaningless because, unfortunately,d i ff erent methods have been used to determine the reported data. This paper focuses on possible variations in people exposure estimate due to the method used to calculate noise levels at receivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…Noise pollution represents a major health problem for the modern world and reducing noise exposure of inhabitants [13] would help avoiding the well-known health effects: sleep disorders [14], learning impairment [15,16], hypertension ischemic heart disease [17,18] and risk for diabetes annoyance [19]. Such noise exposure is generally produced by common source roads [20,21], railway traffic [22], airports [23], and industrial plants [24].…”
Section: Introductionmentioning
confidence: 99%
“…Noise pollution represents a major health problem for the modern world and reducing noise exposure of inhabitants [13] would help avoiding the well-known health effects: sleep disorders [14], learning impairment [15,16], hypertension ischemic heart disease [17,18] and risk for diabetes annoyance [19]. Such noise exposure is generally produced by common source roads [20,21], railway traffic [22], airports [23], and industrial plants [24].…”
Section: Introductionmentioning
confidence: 99%
“…This is a methodology in which the basic measure describing sonorous input is the acoustic indicator already introduced in (2). Like the NMPB, the XP S31-133 standard describes a detailed procedure for calculating acoustic levels, taking into account weather effects (Licitra et al 2012 Based on the results found in the literature (Licitra and Ascari, 2014), the Gden indicator was calculated for the same part of the historic center for which the noise map was developed. Also, the indicator was derived for other towns in Sicily and for other large population centers, so as to compare the results.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…In fact, noise occurring during the landing and takeoff cycles are some of the most undesired environmental issues related to airport operations, and new mitigation measurements are necessary to protect residential areas [4]. Even though comparative analysis of methods to estimate urban noise exposure of inhabitants has been realized [5], a systematic approach to assess the effectiveness of airport noise mitigation strategies has been conducted [6], noise pollution continues to be a major health problem in Europe, with health effects recognized. People perturbed by airport noise may experience a variety of negative responses, such as anger, disappointment, dissatisfaction, withdrawal, helplessness, depression, anxiety, distraction, agitation, or exhaustion (see [7,8]).…”
Section: Introductionmentioning
confidence: 99%